Analysis of the Community Satisfaction Index (IKM) on the Quality of Library Services at the University of Dehasen Bengkulu - Azis Mahyudin; Karona Cahya Susena; Ermy Wijaya (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to examine the quality of service at the Dehasen University Bengkulu library. The method used in analyzing the research data after the data is tabulated is a quantitative descriptive method using community satisfaction index analysis. The results of this study indicate that the services provided by the library staff at Dehasen University of Bengkulu are running well, with an index of 3.201 with a service quality of 80.025 in category B namely the performance of the service unit is good. Although there are 2 indicators that are below the 3.044 interval so that it still has to improve the quakity of it’s service.